Western values of sexual consent in Muhammad Shahrur’s theory of milk al-yamin - Shiddiq, Muhammad Nur; Mukhlas, Oyo Sunaryo; Sar’an, Mohamad; Khaeruman, Badri (International Journal of Nusantara Islam, 2025)
This paper discusses Muhammad Shahrur’s proposal for a “new way” to practice the concept of milk al-yamin in Islam. He believes that the Qur’anic verses pertaining to milk al-yamin can no longer be applied today because of their close connection to slavery. Shahrur argues that the practice of milk al-yamin—particularly in the context of the permissibility of engaging in sexual relations without a marriage contract—can be carried out through mutual consent. This consent is formed through an agreement between a man and a woman, solely for the purpose of engaging in sexual relations. The aim of this paper is to analyze Shahrur’s arguments within the framework of his milk al-yamin theory. The method used in this paper is a normative literature study, employing a juridical-normative approach. The findings of this paper indicate that Shahrur’s theory of milk al-yamin tends to align more closely with Western values of sexual consent than with Islamic values. Moreover, Shahrur’s proposal for milk al-yamin could have significant implications for the development of family law, particularly in Indonesia.